The Influence of Work Stress on Turnover Intention In PT Meadjohnson Indonesia Employees: a Scoping Review - Minarsih Minarsih; M. TaufiQ Noor Rokhman; Ratnawati Ratnawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Previous evaluations of the literature have looked into the connection between work-related stress and intention to leave. This scoping review aims to map out previous research that evaluate the impact of work-related stress on turnover intention. A scoping review goes through the following steps in order: (1) formulate research questions; (2) find pertinent studies; (3) choose studies; (4) plot data; and (5) compile, summarize, and report findings. The scoping review's findings over a ten-year period (2013–2022) indicate that the majority of research acknowledge the impact of work stress on turnover intention. But according to Tarigan (2021) and Agustina (2013), turnover intention is unaffected by work stress.